(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
One of the modern approaches to identifying alternative broad-spectrum against microorganisms that cause human diseases raises an urgent need to search for bioactive compounds with antifungal activity from medicinal plants. One of the main problems of antibiotic therapy for diseases is the development of resistance to opportunistic diseases of relatively low virulence, which are caused by yeast. In this regard, the search for natural medicinal herbs is relevant. The present study was undertaken to evaluate the effectiveness of the antifungal activity of different medicinal plant aqueous extracts: greater burdock (Arctium lappa L.), common wormwood (Artemisia absinthium L.), common thyme (Thymus vulgaris L.), and pot marigold (Calendula officinalis L.) on the growth of yeast: Saccharomyces cerevisiae. Aqueous extracts were prepared from leaves, stems, inflorescences, and roots of ready-made medicinal mix, and their antifungal activity against yeast was tested using the Kirby-Bauer standard disk diffusion method. Disks were soaked in aqueous extracts of medicinal plants and were placed on an agar medium previously inoculated with yeast Saccharomyces cerevisiae as a test object. The prepared agar plates were cultured in the dark at 30°C for 3-5 days. The results obtained showed that the aqueous extracts of medicinal plants demonstrated different antifungal activity concerning test culture, the level of which variable by the plant species. The aquatic extract of medicinal plants: common wormwood (Artemisia absinthium L.), and pot marigold (Calendula officinalis L.) had the most noticeable antifungal activity. The results obtained during the preliminary suggest that the studied aqueous extracts of medicinal plants of natural origin can be used as antifungal agents with a specific mechanism of action.